A comparative case study of well-being in a rural versus an urban coal mining community in Mpumalanga, South Africa. (23rd April 2019) - Baldry, Kim; Patel, Leila; Ross, Eleanor
Given the costs and benefits of mining to local communities, and the difference in availability of resources between rural and urban communities, the study compared well-being in the South African coal mining communities of Chief Albert Luthuli and Mhluzi. Questionnaires were administered to random samples of households from these two communities. Results indicated that both communities could be described as poor in terms of household income, food insecurity, and receipt of social grants; however, poverty levels were more severe in rural Chief Albert Luthuli. While both communities acknowledged the negative environmental impacts of mining, more people in urban Mhluzi felt that their lives had improved and that the benefits of mining outweighed the costs. Overall, well-being was better in the urban than the rural mining community, thereby providing support for the assumption regarding urban-rural differences underpinning the study.